2010
DOI: 10.1194/jlr.m005058
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 LCPUFA from fish oil but not α-linolenic acid-derived LCPUFA confers atheroprotection in mice

Abstract: LCPUFA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) to cardioprotection ( 1, 2 ). As a consequence, increased consumption of food-based sources of EPA and DHA has been recommended in most nutritional guidelines issued by government and health organizations, such as American Heart Association ( 3 ). Although oily fi sh is the richest dietary source of EPA and DHA, its consumption in most Western countries is low and inadequate to provide the recommended daily intake (250-500 mg of EPA and DHA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(64 reference statements)
2
18
1
Order By: Relevance
“…Many of these studies have been carried out in US populations30, 31, 32 that are characterized by low fish consumption,9 and data from the Health Professionals Follow‐up Study suggest that ALA protects against CHD only in this situation 30. In line with this, studies in mice reported that diets rich in ALA are protective against endothelial dysfunction and plaque inflammation,33 although this effect appears to be modest compared with DHA 34. This might explain why, in our population with high fish consumption, we could not detect a cardioprotective effect of ALA; it was probably overrun by the concomitant high intake of EPA and DHA with a stronger benefit against CHD.…”
Section: Discussionmentioning
confidence: 91%
“…Many of these studies have been carried out in US populations30, 31, 32 that are characterized by low fish consumption,9 and data from the Health Professionals Follow‐up Study suggest that ALA protects against CHD only in this situation 30. In line with this, studies in mice reported that diets rich in ALA are protective against endothelial dysfunction and plaque inflammation,33 although this effect appears to be modest compared with DHA 34. This might explain why, in our population with high fish consumption, we could not detect a cardioprotective effect of ALA; it was probably overrun by the concomitant high intake of EPA and DHA with a stronger benefit against CHD.…”
Section: Discussionmentioning
confidence: 91%
“…Our study focused on the hypothesis that dietary enrichment with n-6 PUFAs beyond FADS2 (i.e., GLA) would be as atheroprotective as EO, which we have previously demonstrated as equal to FO in preventing atherosclerosis progression ( 17,41 ). On the other hand, fl axseed oil, which is enriched in ALA, a substrate for FADS2, was not as atheroprotective as FO; this outcome occurred despite signifi cant enrichment of liver PLs with EPA and was likely due to the lower plasma LDL-c concentrations in the FO versus the fl axseed oil group ( 9 ). The combined results of the fl axseed oil and EO studies support our hypothesis that dietary enrichment in n-3 PUFAs beyond FADS2 is atheroprotective.…”
Section: Downloaded Frommentioning
confidence: 68%
“…In other studies investigating the infl uence of dietary n-3 and n-6 PUFAs on atherogenesis, LDL was the predominant plasma atherogenic lipoprotein ( 9,38 ). Differences in plasma apoB lipoprotein response (VLDL vs. LDL) among these studies are likely due to genetic background (LDLrKO vs. apoB100 only-LDLrKO) and diet composition (0.02 vs. 0.2% cholesterol; 10 vs. 20% calories as fat).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons for this. Currently, the richest dietary source of LC3PUFA is marine originated (Degirolamo et al, 2010), making it inappropriate for vegetarians, including ethnic groups who do not consume fish. Equally, many people do not like the taste and/or texture of fish and signs of gastrointestinal upset, fishy aftertaste and repetition have been linked to the use of fish oil supplements (Fetterman and Zdanowicz 2009).…”
Section: Introductionmentioning
confidence: 99%